Digital photogrammetric techniques assessment for the study of the morphology of the dog (canis familiaris) - Wanda Bejarano Concha (2019)
In order to obtain body measurements for the morphological study of the dog through the evaluation of the photogrammetric technique applied to animal husbandry, validated as a modern method for zoometria, capable of creating three-dimensional images from photographs, which can be obtain accurate body measurements, avoiding excessive physical contact with animals, minimizing the stress created through the manipulation of biometrics manual, and likewise with the possibility of transferring the information to be analyzed at any time or place and the possibility of create files with morphological characteristics of each animal, which can be compared to the breed standard. We propose a simple and affordable digital photometry based on allowing the development of a three-dimensional model of the dogs and which can be directly morphometric measures usual in order to obtain data to help us establish general proportions and regional appreciation, both zootechnical and economical, plus you get all kinds of perspectives of individuals. The method also allows comparison of different specimens thus prevents the transfer and handling of the animals.